Novel Nanobiocatalyst Constituted by Lipase from Burkholderia cepacia Immobilized on Graphene Oxide Derived from Grape Seed Biochar - Lays C. de Almeida; Erikles L. O. Andrade; Jefferson C. B. Santos; Roberta M. Santos; Alini T. Fricks; Lisiane dos S. Freitas; Álvaro S. Lima; Matheus M. Pereira; Cleide M. F. Soares (C, 2023)
The present research aims to study the process of immobilization of lipase from Burkholderia cepacia by physical adsorption on graphene oxide derived (GO) from grape seed biochar. Additionally, the modified Hummers method was used to obtain the graphene oxide. Moreover, Fourier transform infrared spectroscopy, Raman spectrum, X-ray diffraction, and point of zero charge were used for the characterization of the GO. The influences of pH, temperature, enzyme/support concentration on the catalytic activity were evaluated for the immobilized biocatalyst. The best immobilization was found (543 ± 5 U/g of support) in the pH 4.0. Considering the biochemical properties, the optimal pH and temperature were 3.0 and 50 °C, respectively, for the immobilized biocatalyst. Reusability studies exhibited that the immobilized lipase well kept 60% of its original activity after 5 cycles of reuse. Overall, these results showed the high potential of graphene oxide obtained from biochar in immobilization lipase, especially the application of nanobiocatalysts on an industrial scale.